2013
DOI: 10.1111/jocn.12316
|View full text |Cite
|
Sign up to set email alerts
|

Instruments for evaluating compliance with infection control practices and factors that affect it: an integrative review

Abstract: Health managers and government policies and interventions should pay greater attention to this subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 49 publications
6
47
0
5
Order By: Relevance
“…6,7,8 In fact, no psychometrically tested observation measures were found in a 2013 integrative review of instruments to measure compliance with infection control practices. 9 There is some evidence that features of the safety climate are related to HCW safety practices, including adherence to SP, [11][12][13][14][15][16] in a systematic review conducted to examine the relationship between patient safety climate and SP we found that despite several high quality studies this topic is underexplored and all studies used different and self-report measures. 17 Because the correlation between observed and reported SP adherence using psychometrically validated tools that account for the features of the safety climate remains unknown, the specific aim of this study was to examine the relationship among these measures of SP adherence and safety climate factors in hospital settings using psychometrically tested instruments.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,8 In fact, no psychometrically tested observation measures were found in a 2013 integrative review of instruments to measure compliance with infection control practices. 9 There is some evidence that features of the safety climate are related to HCW safety practices, including adherence to SP, [11][12][13][14][15][16] in a systematic review conducted to examine the relationship between patient safety climate and SP we found that despite several high quality studies this topic is underexplored and all studies used different and self-report measures. 17 Because the correlation between observed and reported SP adherence using psychometrically validated tools that account for the features of the safety climate remains unknown, the specific aim of this study was to examine the relationship among these measures of SP adherence and safety climate factors in hospital settings using psychometrically tested instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that healthcare workers training along with other factors such as perceptions of safe environment, perception of obstacles to comply with standard precautions and knowledge are strong predictors of compliance with IC standard (18). We found that in comparison with nonteaching hospitals, hand hygiene practices were better in teaching hospitals but antibiotic prophylaxis and safe injection performances were suboptimal.…”
Section: Discussionmentioning
confidence: 56%
“…Some studies have shown that healthcare workers training is one of the strong predictors of compliance with IC standards (18). In this study we found that only one third of the midwives took part in IC training courses.…”
Section: Discussionmentioning
confidence: 57%
“…A review of factors that influence adherence indicates that variables like the organizational safety climate, perceived obstacles, professional degree, care delivery to a smaller number of patients, risk personality and self-efficacy should not be ignored. (26) …”
Section: Discussionmentioning
confidence: 99%